Ceramic base and manufacturing method thereof

By using the optimal ratio of aluminum oxide and aluminum nitride in the ceramic base and adding dopants, the problem of reduced volume resistance at high temperature and low thermal conductivity at room temperature is solved, and efficient thermal conductivity and resistance performance are achieved.

CN119874334AActive Publication Date: 2025-04-25KSM COMPONENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410845666.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-25
Filing Date
2024-06-27
Publication Date
2025-04-25
Estimated Expiration
2044-06-27

AI Technical Summary

Technical Problem

The volume resistance of the existing ceramic base drops sharply at high temperatures, resulting in leakage current and low thermal conductivity at room temperature, resulting in large deviations in temperature consistency, reduced output and shortened product life.

Method used

Ceramic bases containing alumina and aluminum nitride are used and mixed at the optimal ratio to avoid the formation of alumina oxide phases, combined with dopants such as magnesium oxide, yttrium oxide, graphene and rare earth composite oxides to improve thermal conductivity and volume resistance.

Benefits of technology

It has achieved high volume resistance at high temperatures above 500℃, prevent leakage current, and have high thermal conductivity at room temperature, which solves the problems of temperature consistency deviation and yield reduction, and extends the product life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874334A_ABST
    Figure CN119874334A_ABST
Patent Text Reader

Abstract

Disclosed are a ceramic susceptor and a method for manufacturing the same, the ceramic susceptor particularly having excellent volume resistance at high temperature and thermal conductivity at normal temperature compared to conventional ceramic susceptors. The ceramic base contains aluminum oxide (Al2O3) and aluminum nitride (AlN), and does not contain a second phase including an aluminum oxynitride phase (AlON phase).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a ceramic susceptor and a method for manufacturing the same, and more particularly to a ceramic susceptor having a volume resistance at high temperature and a thermal conductivity at room temperature that are superior to those of a conventional ceramic susceptor and a method for manufacturing the same. Background Art

[0002] As semiconductor processes become increasingly miniaturized and highly integrated, the use of high-power plasma is inevitable. Therefore, vacuum plasma equipment using high-temperature plasma is widely used in the etching of semiconductor elements or other process fields for realizing ultra-fine shapes. Moreover, as these vacuum plasma equipment, there are, for example: PECVD (plasma enhanced chemical vapor deposition) equipment that forms a vapor-deposited film on a substrate by chemical evaporation using plasma; sputtering equipment that forms a vapor-deposited film in a physical manner; and dry etching equipment for etching a substrate or a substance coated on a substrate into a specific pattern.

[0003] However, since high-temperature plasma is generated inside the vacuum plasma equipment, the cavity and the parts inside it will inevitably be damaged. In addition, specific elements and contamination particles are generated from the surface of the cavity and the parts inside it, which may pollute the inside of the cavity. Especially in plasma etching equipment, since reactive gases such as F and Cl are injected under the plasma atmosphere, the inner wall of the cavity and its internal parts can only be in an extremely harsh corrosive environment. Generally speaking, these corrosions will first cause chemical and physical damage to the cavity and the parts inside it, and secondly, they will produce pollutants and particles, which will lead to an increase in the defective rate and a decrease in quality of the products made through the process inside the cavity.

[0004] Moreover, if the cavity and the parts inside it are damaged, it is necessary to replace, clean, or repair the damaged part of the equipment, which incurs additional costs and requires the process production line to be stopped, which increases the process time required for product manufacturing. For these reasons, the previous metal bases set inside the cavity are replaced by ceramic bases. As these ceramic bases, aluminum nitride (AlN) sintered bodies or aluminum oxide (Al2O3) sintered bodies with excellent thermal conductivity can be listed. Moreover, these ceramic bases are mainly used for heaters or electrostatic chucks for semiconductor manufacturing processes.

[0005] Aluminum nitride has physical properties such as being stable at high temperatures and having excellent electrical insulation and thermal conductivity. In addition, it has a thermal expansion coefficient similar to that of silicon, and is therefore mainly used in semiconductor manufacturing equipment that requires high electrical resistance at high temperatures. Aluminum oxide is also a material that is stable at high temperatures, and has better electrical insulation and higher hardness than aluminum nitride.

[0006] On the other hand, in recent years, although the semiconductor process has been developing in the direction of process miniaturization and large-diameter equipment for improving production, various problems have arisen in the semiconductor manufacturing process due to such process miniaturization and large-diameter equipment. Therefore, a new generation of semiconductor process technology that can overcome these problems is needed. Therefore, the process is carried out in a more severe environment of 600-700°C. In order to withstand this environment, the ceramic base must meet the ceramic characteristics of a volume resistivity of 1.0E+10-1.0E+13Ω·cm at 500°C and a thermal conductivity of 30W / mk or more, preferably 40W / mk or more at room temperature.

[0007] However, there is a problem that, for aluminum nitride, at 500°C, the volume resistivity drops sharply and leakage current tends to occur, while for aluminum oxide, the thermal conductivity at room temperature is very low, at the level of 20 to 30 W / mk. If the thermal conductivity at room temperature is only 20 to 30 W / mk, problems such as increased temperature uniformity deviation and reduced production will occur. Moreover, in the case of a large deviation in the temperature uniformity of thermal conductivity, the life of the product may be shortened due to thermal stress and thermal shock. Therefore, a ceramic base is required that has a high volume resistivity even at temperatures above 500°C to prevent leakage current and a high thermal conductivity at room temperature. Summary of the invention

[0008] Problems to be solved by the invention

[0009] Therefore, an object of the present invention is to provide a ceramic susceptor having a volume resistance at high temperature and a thermal conductivity at room temperature superior to those of a conventional ceramic susceptor, and a method for producing the same.

[0010] Means for solving problems

[0011] To achieve the above object, the present invention provides a ceramic susceptor comprising aluminum oxide (Al2O3) and aluminum nitride (AlN) and excluding a second phase including an aluminum oxynitride phase (AlON phase).

[0012] Furthermore, the present invention provides a ceramic base, which includes aluminum oxide (Al2O3) and a dopant, wherein the dopant includes any one or more of magnesium oxide (MgO), yttrium oxide (Y2O3), graphene, and a rare earth composite oxide.

[0013] In addition, the present invention provides a method for manufacturing a ceramic base, which includes: step a), mixing aluminum oxide (Al2O3), aluminum nitride (AlN), an alcohol compound and a binder; step b), drying the mixture to produce a powder after removing the alcohol compound component; step c), compressing and molding the dried powder to produce a preform processed into a certain shape; step d), degreasing the prepared preform to remove the binder component; and step e), sintering and grinding the degreased preform.

[0014] In addition, the present invention provides a method for manufacturing a ceramic base, which includes: step a), mixing aluminum oxide (Al2O3), a dopant, an alcohol compound and a binder; step b), drying the mixture to produce a powder from which the alcohol compound component is removed; step c), compressing and molding the dried powder to produce a preform processed into a certain shape; step d), degreasing the prepared preform to remove the binder component; and step e), sintering and grinding the degreased preform, wherein the dopant includes any one or more of magnesium oxide (MgO), yttrium oxide (Y2O3), graphene and rare earth composite oxides.

[0015] Effects of the Invention

[0016] The ceramic susceptor and the method for manufacturing the same provided by the present invention have advantages that the volume resistance at high temperature and the thermal conductivity at room temperature are superior to those of a conventional ceramic susceptor. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 1 is an XRD graph showing the physical property values ​​of the ceramic susceptor that vary depending on the sintering temperature.

[0018] Figure 2 This is a graph showing the correlation between the content of aluminum oxide and the sintering temperature. DETAILED DESCRIPTION

[0019] Hereinafter, the present invention will be described in detail.

[0020] One embodiment (first embodiment) of the present invention provides a ceramic base including aluminum oxide (Al 2 O 3 ) and aluminum nitride (AlN) and does not include a second phase including an aluminum oxynitride phase (AlON phase).

[0021] As semiconductor processes become increasingly miniaturized and highly integrated, the use of high-power plasma is inevitable. Therefore, vacuum plasma equipment using high-temperature plasma has been widely used to achieve etching of semiconductor elements or other ultra-fine shapes. In response to this, ceramic bases composed of aluminum nitride (AlN) sintered bodies or aluminum oxide (Al2O3) sintered bodies with better plasma corrosion resistance are being used in this field to replace the previous metal bases. In particular, in recent years, in order to achieve process miniaturization and large-diameter equipment for the purpose of increasing the yield in semiconductor processes, semiconductor manufacturing processes are carried out in a more severe environment of 600 to 700°C. In order to withstand this environment, the ceramic base must meet the ceramic properties of a volume resistivity of 1.0E+10 to 1.0E+13Ω·cm at 500°C and a thermal conductivity of 30W / mk or more, preferably 40W / mk or more at room temperature.

[0022] However, there is a problem that, for aluminum nitride, the volume resistivity drops sharply at 500°C, and there is a tendency to generate leakage current. For aluminum oxide, the thermal conductivity at room temperature is very low, at the level of 20 to 30 W / mk. If the thermal conductivity at room temperature is only 20 to 30 W / mk, there will be problems such as large deviation in temperature uniformity and reduced production. Moreover, in the case of large deviation in temperature uniformity of thermal conductivity, the life of the product may be shortened due to thermal stress and thermal shock. In response to this, after multi-angle research, the applicant has invented a ceramic base that can be used at high temperatures above 500°C. Even at temperatures above 500°C, the ceramic base has a high volume resistivity, can prevent leakage current, and has a higher thermal conductivity at room temperature than usual, thereby solving the above problems.

[0023] The ceramic base provided in the first embodiment of the present invention is a sintered body containing aluminum oxide (Al2O3) and aluminum nitride (AlN) as main phases, wherein the aluminum oxide not only has excellent electrical insulation and high hardness but is also stable at high temperatures, and the aluminum nitride has physical properties of being stable at high temperatures and having excellent electrical insulation and thermal conductivity.

[0024] In particular, the present invention makes up for all the problems that occur when aluminum oxide and aluminum nitride are used separately and the problems that occur when aluminum oxide and aluminum nitride are not mixed at the optimal ratio by mixing the aluminum oxide and aluminum nitride at the optimal ratio. Specifically, when aluminum oxide and aluminum nitride are mixed at the optimal ratio as in the present invention, as shown in Table 5 described later, the state presented is that the crystal phase does not change, such as the second phase such as the aluminum oxynitride phase (phase) is not generated (that is, the second phase including the aluminum oxynitride phase is not included), and the aluminum oxide phase and the aluminum nitride phase are uniformly mixed and distributed, thereby maximizing the physical properties of the base. In addition, in the process of manufacturing the ceramic base, the sintering process is performed at an optimal temperature (less than 1,650°C, preferably a temperature of 1,300°C or more and less than 1,650°C), so that the generation of the second phase can be more thoroughly prevented. Furthermore, the ceramic base thus satisfies ceramic characteristics that the volume resistivity at 500° C. is 1.0E+10 to 1.0E+13 Ω·cm and the thermal conductivity at room temperature is 30 W / mk or more.

[0025] The ceramic base provided in the first embodiment of the present invention contains more than 68% by weight and less than 99.8% by weight, preferably 70-95% by weight, more preferably 70-80% by weight, and most preferably 73-77% by weight of aluminum oxide. In addition, the ceramic base provided in the first embodiment of the present invention contains more than 0.2% by weight and less than 32% by weight, preferably 5-30% by weight, more preferably 20-30% by weight, and most preferably 23-27% by weight of aluminum nitride. If the aluminum oxide and aluminum nitride cannot each meet the content range, the volume resistance at 500°C or the thermal conductivity at room temperature cannot meet the required conditions, and the ceramic base will not meet the ceramic characteristics that the volume resistance at 500°C must be 1.0E+10~1.0E+13Ω·cm and the thermal conductivity at room temperature must be 30W / mk or more.

[0026] The purity of the aluminum oxide and aluminum nitride is preferably 99% or more, respectively. The particles of these particles are preferably nano-sized. They are preferably all used in the form of powders.

[0027] More specifically, the aluminum oxide particles may have a size ranging from nanometers to micrometers. For example, the aluminum oxide particles may be obtained by mixing aluminum oxide particles of 3 to 5 μm in size and aluminum oxide particles of 50 nm in size at a weight ratio of about 7:3, and then crushing the particles by ball milling. The present invention is not limited to the above examples, and for example, the particle size and mixing ratio may be varied, and the ball milling process may be excluded.

[0028] Furthermore, the average particle size (D50) of the aluminum nitride particles can be 0.5 to 1.5 μm, preferably 0.8 to 1.3 μm, and more preferably 0.9 to 1.2 μm. If the average particle size (D50) of the aluminum nitride particles is less than 0.5 μm, the reaction temperature becomes low, which may cause a problem of reacting with aluminum oxide at low temperatures to generate a second phase. Furthermore, when the average particle size (D50) of the aluminum nitride particles exceeds 1.5 μm, it will not form a close-packed / tightly packed structure with aluminum oxide, resulting in a problem of decreased density during final sintering. Furthermore, in the present invention, it is preferred to exclude nano-sized aluminum nitride particles as much as possible.

[0029] On the other hand, the ceramic base provided in the first embodiment may further include a dopant as required. The dopant may be used to further improve the thermal conductivity of the ceramic base.

[0030] For example, when a conventional sintered body is applied to a substrate and a semiconductor ceramic heater or electrostatic chuck is used at a high temperature of 500°C or above, the substrate may be broken due to thermal shock because it cannot follow the rapid change in the temperature of the heating element. However, if a dopant is mixed in to improve the thermal shock resistance of the substrate and applied to the heater or electrostatic chuck, the heat of the heating element can be efficiently transferred to prevent the substrate from breaking due to thermal shock.

[0031] Furthermore, examples of the dopant of the present invention include any one or more of magnesium oxide (MgO), yttrium oxide (Y 2 O 3 ), graphene, and rare earth composite oxides.

[0032] In the case where the dopant is also included in the ceramic base, the dopant may be included in an amount of 0.05 to 2 parts by weight, preferably 0.1 to 1 part by weight, and more preferably 0.2 to 0.8 parts by weight relative to 100 parts by weight of the total weight of the aluminum oxide and the aluminum nitride. If the dopant is included in an amount of less than 0.05 parts by weight, or is not included at all, relative to 100 parts by weight of the total weight of the aluminum oxide and the aluminum nitride, the same problems that have occurred in the past may occur, or the effect that can be obtained by using the dopant will be significantly reduced, the degree of improvement in thermal conductivity will be very small, and there may be a problem of unsintering. In addition, when the content of the dopant exceeds 2 parts by weight relative to 100 parts by weight of the total weight of the aluminum oxide and the aluminum nitride, the dispersion effect becomes poor, the thermal conductivity will be reduced, and there may be a tendency for the sintered density to become lower, and there may also be a problem that the color of the product becomes darker or the color of the dopant is presented in its original form due to the influence of the dopant. In addition, the dopants suitable for use in the present invention all have a purity of 99% or more. Furthermore, it is preferable that 0.05 to 0.5 wt % of each dopant is contained.

[0033] Magnesium oxide as one of the dopants may be included for the purpose of improving the thermal conductivity and volume resistivity of the ceramic base. The magnesium oxide may induce the formation of MgAl2O4 phase or MgAlON phase by sintering with the aluminum oxide and / or aluminum nitride, but if the MgAl2O4 phase or MgAlON phase is excessively generated, it may cause the density to become low, which in turn may reduce the thermal conductivity. Therefore, even if the same components are used, the content of each component must be adjusted. For example, in the present invention, the content of any one or more of the MgAl2O4 phase and the MgAlON phase contained in the final ceramic base may be less than 1% by weight relative to the total weight of the ceramic base, preferably less than 0.8% by weight, and more preferably less than 0.6% by weight. Moreover, the particle size of the magnesium oxide is not particularly limited, but it is preferred to exclude nano-sized particles that will have a relatively weak effect.

[0034] The yttrium oxide (Y2O3) may be included for the purpose of improving the thermal conductivity of the ceramic base. The purity of the yttrium oxide is preferably 99% or more. In terms of improving physical properties by densification, it is suitable that the yttrium oxide particles have a nanometer size, and it is preferred to use these yttrium oxides in the form of powder. More specifically, the average particle size (D50) of the yttrium oxide particles can be 50 to 150 nm, preferably 70 to 120 nm, and more preferably 90 to 100 nm. If the average particle size (D50) of the yttrium oxide particles is less than 50 nm, even if a trace amount of yttrium oxide is included, due to the characteristics of the nano-scale yttrium oxide powder, it is possible that the sintered body has the color of the yttrium oxide particles (yellow, etc.). In addition, when the average particle size (D50) of the yttrium oxide particles exceeds 150 nm, an incomplete sintered body is formed during sintering, which may cause a problem of reduced thermal conductivity due to a decrease in density. These problems may be more obvious, especially when the average particle size (D50) of the yttrium oxide particles is in the micrometer range.

[0035] The graphene may also be included for the purpose of improving the thermal conductivity of the ceramic base. The purity of the graphene is preferably 99% or more, and the graphene particles have a nanometer size, and these graphenes are preferably used in the form of powder (graphene nanopowder (Graphene nanopowder), GNP). More specifically, the average particle size (D50) of the graphene particles can be 0.1 to 1.5nm, preferably 0.3 to 1nm, and more preferably 0.5 to 0.8nm. If the average particle size (D50) of the graphene particles is less than 0.1nm, it fails to become a sufficient size to play a bridging role between the graphene particles, and the effect of improving the thermal conductivity may be minimal or ineffective. In addition, when the average particle size (D50) of the graphene particles exceeds 1.5nm, these graphene particles may be intertwined and difficult to disperse, which may cause the problem of decreased thermal conductivity due to decreased density.

[0036] Finally, the rare-earth composite oxide contains two or more rare-earth metals selected from the group consisting of scandium (Sc), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (YB) and lutetium (Lu). The purity of the rare-earth composite oxide containing such rare-earth metals is preferably 99% or more. The properties of the rare-earth composite oxide are preferably powders, and the size of the powder particles is not particularly limited.

[0037] The rare earth composite oxide can further improve the thermal conductivity of the ceramic base, and by using the rare earth composite oxide, the time required for desorption can be reduced. As mentioned above, the rare earth composite oxide contains two or more rare earth metals, and can contain preferably 2 to 5 different rare earth metals.

[0038] As the rare earth composite oxide containing 2 to 5 different rare earth metals, the following composite oxides can be exemplified: composite oxides containing two different rare earth metals, such as europium-gadolinium composite oxide (EuGdO X ), samarium-gadolinium composite oxide (SmGdO X ), cerium-europium composite oxide (CeEuO X ), samarium-cerium composite oxide (SmCeO X ), gadolinium-samarium composite oxide (GdSmO X ) and lanthanum-cerium composite oxide (LaCeO X); composite oxides containing three different rare earth metals, such as samarium-cerium-europium composite oxide (SmCeEuO X ), gadolinium-cerium-lanthanum composite oxide (GdCeLaO X ) and europium-gadolinium-samarium composite oxide (EuGdSmO X ); composite oxides containing four different rare earth metals, such as samarium-cerium-gadolinium-europium composite oxide (SmCeGdEuO X ) and gadolinium-samarium-europium-lanthanum composite oxide (GdSmEuLaO X ); and composite oxides containing five different rare earth metals, such as samarium-cerium-europium-gadolinium-lanthanum composite oxide (SmCeEuGdLaO X ), in addition, as long as it is a composite oxide containing 2 to 5 different rare earth metals (oxides), it can be used without particular limitation.

[0039] The rare earth composite oxide containing 2 to 5 different rare earth metals may contain a variety of different rare earth metals in a variety of ratios. For example, the rare earth composite oxide containing 2 to 5 different rare earth metals may be appropriately blended in such a way that the target effect of the rare earth composite oxide is maximized, for example, containing two rare earth metals (oxides) in a weight ratio of 2.5 to 3.5:1, or containing three rare earth metals (oxides) in a weight ratio of 1 to 3.5:0.5 to 2.5:1, or containing four rare earth metals (oxides) in a weight ratio of 1.5 to 3.5:0.5 to 2.5:1 to 2.5:1, or containing five rare earth metals (oxides) in a weight ratio of 1 to 3:0.5 to 1.5:0.5 to 1.5:1 to 2:1. For example, in terms of the weight ratio of each rare earth metal (oxide), SmCeEuO X The ratio can be 2:1:1, GdCeLaO X Can be 3:2:1, EuGdSmO X Can be 1.5:1.5:1, SmCeGdEuO X Can be 2:1:1.5:1, GdSmEuLaO X Can be 3:2:2:1, SmCeEuGdLaO X It can be 2:1:1:1.5:1.

[0040] In the rare earth composite oxide, any one rare earth metal can be dissolved in the remaining one (or any one) rare earth metal oxide. As a result, the crystallization of the rare earth metal oxide changes, and the rare earth composite oxide can increase oxygen lattice defects compared to a single rare earth metal oxide. In this way, the interfacial reactivity of the rare earth composite oxide with increased oxygen lattice defects is enhanced, and thus it can effectively react with the interface or lattice oxygen of each component in the ceramic base.

[0041] Examples of rare earth metal oxides containing one rare earth metal include scandium oxide (Sc2O3), lanthanum oxide (La2O3), cerium oxide (CeO2), praseodymium oxide (Pr6O3), and 11 ), neodymium oxide (Nd2O3), promethium oxide (Pm2O3), samarium oxide (Sm2O3), europium oxide (Eu2O3), gadolinium oxide (Gd2O3), terbium oxide (Tb4O7), dysprosium oxide (Dy2O3), holmium oxide (Ho2O3), erbium oxide (Er2O3), thulium oxide (Tm2O3), ytterbium oxide (YB2O3) and lutetium oxide (Lu2O3), but the dopant of the present invention does not include rare earth metal oxides containing only one rare earth metal.

[0042] On the other hand, in the above description, the dopant includes any one or more of the remaining rare earth metal oxides except magnesium oxide, yttrium oxide, graphene and yttrium oxide. Among them, as the dopant of the present invention, it is suitable to basically include magnesium oxide. Moreover, it is preferred to use magnesium oxide and graphene together as dopants. Moreover, it is more preferred to use magnesium oxide, graphene and yttrium oxide together as dopants. Moreover, it is most preferred to use magnesium oxide, graphene, yttrium oxide and rare earth composite oxides together as dopants.

[0043] When magnesium oxide and graphene are used together as dopants, 0.05 to 0.5 parts by weight of magnesium oxide and 0.05 to 0.5 parts by weight of graphene may be included based on 100 parts by weight of the total weight of aluminum oxide and aluminum nitride.

[0044] Furthermore, when magnesium oxide, graphene and yttrium oxide are used together as dopants, 0.05 to 0.5 parts by weight of the magnesium oxide, 0.05 to 0.5 parts by weight of the graphene, and 0.05 to 0.5 parts by weight of the yttrium oxide may be included, relative to 100 parts by weight of the total weight of the aluminum oxide and aluminum nitride.

[0045] Furthermore, when magnesium oxide, graphene, yttrium oxide and rare earth composite oxide are used together as dopants, relative to 100 parts by weight of the total weight of the aluminum oxide and aluminum nitride, 0.05 to 0.5 parts by weight of the magnesium oxide, 0.05 to 0.5 parts by weight of the graphene, 0.05 to 0.5 parts by weight of the yttrium oxide, and 0.05 to 0.5 parts by weight of the rare earth composite oxide may be included.

[0046] Next, the ceramic base provided by the second embodiment of the present invention is described. The ceramic base provided by the second embodiment of the present invention comprises aluminum oxide (Al2O3) and a dopant, wherein the dopant comprises any one or more of magnesium oxide (MgO), yttrium oxide (Y2O3), graphene, and a rare earth composite oxide.

[0047] The applicant has confirmed that, in addition to the ceramic susceptor provided by the first embodiment described above, the ceramic susceptor provided by the second embodiment also has excellent volume resistance and thermal conductivity. The ceramic susceptor provided by the second embodiment will be described in detail below.

[0048] The ceramic base provided in the second embodiment has a structure in which only aluminum nitride is excluded from the ceramic base of the first embodiment in which the dopant is also included. Here, the content of the aluminum oxide is the remainder excluding the total content of the dopant. Specifically, the dopant may be included in an amount of 0.05 to 2% by weight, preferably 1 to 2% by weight, and more preferably 1.5 to 2% by weight relative to the total weight of the ceramic base. Furthermore, the aluminum oxide may be included in an amount of 98 to 99.95% by weight, preferably 98 to 99% by weight, and more preferably 98 to 98.5% by weight relative to the total weight of the ceramic base. If the content of the aluminum oxide and the dopant is not within the content range, the present invention will not show the target volume resistivity characteristics and thermal conductivity characteristics, etc.

[0049] Moreover, the dopants suitable here all have a purity of more than 99%. Moreover, it is preferred to contain 0.05 to 0.5 weight % of each dopant. On the other hand, in the case where the ceramic base provided in the second embodiment contains magnesium oxide (MgO) as a dopant, it is possible that a MgAl2O4 spinel phase is formed due to the sintering reaction of aluminum oxide and magnesium oxide. If the MgAl2O4 spinel phase is excessively generated, the thermal conductivity will decrease, so even if the same components are used, the content of each component must be adjusted.

[0050] On the other hand, the above describes the case where the dopant includes any one or more of the remaining rare earth metal oxides other than magnesium oxide, yttrium oxide, graphene, and yttrium oxide. Among them, the ceramic base suitable for the second embodiment also basically contains magnesium oxide as a dopant in the same way as the first embodiment. Moreover, it is preferred to use magnesium oxide and graphene together as dopants. Moreover, it is more preferred to use magnesium oxide, graphene, and yttrium oxide together as dopants. Moreover, it is most preferred to use magnesium oxide, graphene, yttrium oxide, and rare earth composite oxides together as dopants.

[0051] If magnesium oxide and graphene are used together as dopants, the magnesium oxide may be contained in an amount of 0.05 to 0.5 wt %, and the graphene may be contained in an amount of 0.05 to 0.5 wt %.

[0052] Furthermore, when magnesium oxide, yttrium oxide, and graphene are used together as dopants, 0.05 to 0.5 wt % of the magnesium oxide, 0.05 to 0.5 wt % of the yttrium oxide, and 0.05 to 0.5 wt % of the graphene may be included.

[0053] In particular, when magnesium oxide, yttrium oxide, graphene and rare earth composite oxides are used together as dopants, the magnesium oxide may be included in an amount of 0.05 to 0.5 weight %, the yttrium oxide may be included in an amount of 0.05 to 0.5 weight %, the graphene may be included in an amount of 0.05 to 0.5 weight %, and the rare earth composite oxide may be included in an amount of 0.05 to 0.5 weight %.

[0054] As mentioned above, the volume resistivity of the ceramic base provided by the present invention at 500°C is 1.0E+10 to 1.0E+13Ω·cm, and its thermal conductivity at room temperature is 30W / mk or more, preferably 40 to 60W / mk. That is, only when the ceramic heater satisfies both the volume resistivity at 500°C and the thermal conductivity at room temperature, can the purpose of the present invention be achieved.

[0055] If the volume resistivity cannot be met, it will be difficult to apply the ceramic base to the next generation semiconductor manufacturing process. Even if it is applied, the leakage current may increase sharply. In addition, if the thermal conductivity cannot be met, the temperature uniformity deviation will increase, resulting in reduced production and other problems, and the product life may be shortened due to thermal stress and thermal shock.

[0056] Next, the method for manufacturing the ceramic base provided by the present invention is described.

[0057] First, the manufacturing method of the ceramic base provided in the first embodiment includes: step a), mixing aluminum oxide (Al2O3), aluminum nitride (AlN), an alcohol compound and a binder; step b), drying the mixture to produce a powder after removing the alcohol compound component; step c), compressing and molding the dried powder to produce a preform processed into a certain shape; step d), degreasing the prepared preform to remove the binder component; and step e), sintering and grinding the degreased preform.

[0058] Furthermore, a dopant may be added and mixed in step a) as required, and examples of such dopant include any one or more of magnesium oxide (MgO), yttrium oxide (Y2O3), graphene, and rare earth composite oxides.

[0059] The alcohol compound used in step a) is used to properly mix these raw materials, and examples thereof include alcohol compounds with carbon numbers of 1 to 5, specifically ethanol, methanol, and isopropanol, etc. Similarly, the binder used in step a) is used to improve the binding force of these raw materials, and examples thereof include polyvinyl alcohol (PVA) and polyvinyl butyral (PVB), etc.

[0060] The step b) is a step of drying the powder mixture mixed in the step a) to remove the alcohol component. The drying can be carried out by methods well known in the art, such as spray drying and vacuum drying. The drying time can be widely used according to the physical properties of the target ceramic base.

[0061] The step c) is a step of compressing and molding the dried powder to produce a preform processed into a certain shape. The compression molding is a first molding (i.e., first molding) process for controlling the powder dried in the step b) to a target size and shape, and examples thereof include stamping molding and the like. At this time, in order to manufacture products with denser specifications, cold isostatic pressing (CIP) can also be performed as needed. The stamping molding is preferably performed at room temperature and general atmospheric pressure, but is not limited thereto, and the atmosphere during molding is sufficient as long as it does not affect the molding of the mixture. In addition, after the molding process of the step c) is performed, the preform can be manufactured by processing by green body processing (performed before sintering, also referred to as unprocessed) and the like.

[0062] The step d) is a step of degreasing the preform to remove the binder component. The degreasing is a process for removing the binder and greasy contaminants, and can be performed at a temperature of 350-600° C. within 60 hours.

[0063] The step e) is a step of sintering (second molding) and grinding the degreased preform to manufacture a ceramic substrate. The sintering is a second molding (i.e., second molding) process for further improving the volume resistivity of the ceramic base, etc., and preferably utilizes a hot press (Hot Press) sintering method. In addition, when the degreased preform is sintered at a temperature above 1,650°C, aluminum oxide reacts with aluminum nitride to form an aluminum oxynitride phase, which causes a problem of reduced thermal conductivity. Therefore, the sintering in the step e) must be performed at a temperature less than 1,650°C, preferably above 1,300°C and less than 1,650°C.

[0064] Furthermore, the second embodiment provides a method for manufacturing a ceramic base, including: step a), mixing aluminum oxide (Al2O3), a dopant, an alcohol compound and a binder; step b), drying the mixture to produce a powder after removing the alcohol compound component; step c), compressing and molding the dried powder to produce a preform processed into a certain shape; step d), degreasing the prepared preform to remove the binder component; and step e), sintering and grinding the degreased preform, wherein the dopant includes any one or more of magnesium oxide (MgO), yttrium oxide (Y2O3), graphene and rare earth composite oxides.

[0065] The ceramic susceptor of the present invention manufactured by the above manufacturing method can be widely used in semiconductor manufacturing process devices or components, and is preferably used as a material for a heater or an electrostatic chuck for semiconductor manufacturing process. The application field is not particularly limited, and it can also be used in the field of using ceramic materials in a high-temperature plasma environment.

[0066] The present invention will be described in more detail below through specific examples. The following examples are intended to illustrate the present invention, but the present invention is not limited to the following examples.

[0067] [Examples 1 to 8, Comparative Examples 1 to 8] Ceramic base manufacturing

[0068] The raw materials were mixed with the composition shown in Table 1 below, and a small amount of ethanol and polyvinyl butyral (binder) were mixed and dried. The dried mixture was then press-formed and processed to produce a preform, and then degreased at 500°C for 30 hours. The degreased preform was sintered and ground in a high-temperature pressure sintering furnace (250 bar pressure, 1,630°C temperature) to produce a ceramic base.

[0069]

Table 1

[0070]

[0071] *Dopant unit: weight %

[0072] * Rare earth composite oxide: Ceria-doped Samarium (CDS) [Experimental Example 1] Volumetric conductivity of ceramic base Resistance and thermal conductivity evaluation (1)

[0073] After applying a voltage of 500 V / mm to each of the ceramic bases produced in Examples 1 to 8 and Comparative Examples 1 to 8, the current was measured (measured in a vacuum atmosphere and at room temperature) after one minute had passed, and the volume resistivity was calculated. The results are shown in Table 2 below.

[0074] Furthermore, for each ceramic base manufactured in Examples 1 to 8 and Comparative Examples 1 to 8, samples were prepared using LFA 467 equipment from NETZSCH according to ASTM C0408-88R11, and then measured at room temperature to calculate the thermal conductivity. The results are also shown in Table 2 below.

[0075] In addition, the density value of each of the ceramic susceptors manufactured in Examples 1 to 8 and Comparative Examples 1 to 8 was calculated by the Archimedean method, and the results are also shown in Table 2 below.

[0076]

Table 2

[0077]

[0078] The volume resistivity and thermal conductivity of each ceramic base manufactured in Examples 1 to 8 and Comparative Examples 1 to 8 were measured, and the results are shown in Table 2. The ceramic bases of Examples 1 to 8 all meet the volume resistivity (1.0E+10Ω·cm to 1.0E+13Ω·cm) at 500°C required by the new generation semiconductor manufacturing process.

[0079] Furthermore, with respect to thermal conductivity, from the comparison between Examples 1 and 2 and Comparative Examples 1 and 2, the comparison between Examples 3 and 4 and Comparative Examples 3 and 4, the comparison between Examples 5 and 6 and Comparative Examples 5 and 6, and the comparison between Examples 7 and 8 and Comparative Examples 7 and 8, it can be confirmed that Examples 1 to 8 using each dopant at a content of 0.05 to 0.5 wt %, respectively, are superior to Comparative Examples 1 to 8 using any dopant at a content exceeding 0.05 to 0.5 wt %.

[0080] In particular, in Examples 7 and 8, in which all dopants were used in contents of 0.05 to 0.5 wt %, respectively, the thermal conductivity at room temperature exceeded 40 W / mk.

[0081] Furthermore, when comparing Example 2 with Comparative Example 2, Example 2 used 0.5 wt% MgO, while Comparative Example 2 used 1 wt% MgO. Although the difference in content was not significant, the thermal conductivity dropped sharply when the MgO content increased from 0.5 wt% to 1 wt%. This is because if the MgO content exceeded 0.5 wt%, an excessive amount (exceeding 0.6 wt%) of MgAl2O4 phase or MgAlON phase was generated in the final product, resulting in an increase in the fraction. This result can be confirmed by the following Table 3.

[0082]

Table 3

[0083]

[0084] *Dopant unit: weight %

[0085] [Production Examples 1 to 7] Manufacturing and physical property evaluation of ceramic base

[0086] In order to derive the optimal mixing ratio of aluminum oxide and aluminum nitride, a ceramic base containing only aluminum oxide and aluminum nitride at the ratio shown in Table 4 below was manufactured (the manufacturing method was the same as that of Example 1 except for the composition).

[0087] The volume resistivity, thermal conductivity, etc. of each of the produced ceramic bases were measured, and the results are shown in the following Table 5 (the experimental conditions, etc. were the same as those of Experimental Example 1).

[0088]

Table 4

[0089] <![CDATA[Al2O3:AlN (weight ratio)]]> Production Example 1 100:0 Production Example 2 99.8:0.2 Production Example 3 95:5 Production Example 4 85:15 Production Example 5 75:25 Production Example 6 68:32 Production Example 7 60:40

[0090]

Table 5

[0091]

[0092] *Al2O3 and AlN units: weight %

[0093] It can be confirmed from Tables 4 and 5 that the ratio of the aluminum nitride phase varies depending on the addition ratio of aluminum nitride, thereby varying the volume resistance at high temperature and the thermal conductivity at room temperature.

[0094] More specifically, the changes in physical property values ​​according to the addition ratio of aluminum nitride were confirmed, and after XRD, no aluminum oxynitride phase was generated in the final products of Manufacturing Examples 1 to 7. Moreover, the volume resistivity and thermal conductivity of Manufacturing Examples 3 to 5 all met the requirements, and Manufacturing Example 5, which mixed aluminum oxide and aluminum nitride at a weight ratio of 75:25, was the best overall.

[0095] Therefore, if the aluminum nitride content is too small, the Al2O3 phase is formed as the main phase, and there is almost no effect of improving thermal conductivity. If the aluminum nitride content is too large, the ratio of the AlN phase becomes high. Although it has the effect of improving thermal conductivity, the volume resistance and hardness tend to decrease.

[0096] [Production Examples 5-1 to 5-5] Evaluation of physical properties of ceramic base based on sintering temperature

[0097] In Manufacturing Example 5, alumina and aluminum nitride were mixed in a weight ratio of 75:25, which was the best overall. Based on this result, as shown in Table 6 below, a ceramic base was manufactured by setting only the sintering temperature differently (except for the composition and sintering temperature, the manufacturing method is the same as that of Example 1).

[0098] Then, the volume resistivity, thermal conductivity, etc. of each of the produced ceramic bases were measured, and the results are shown in the following Table 7 (the experimental conditions, etc. were the same as those of Experimental Example 1).

[0099]

Table 6

[0100] <![CDATA[Al2O3:AlN (weight ratio)]]> Sintering temperature(℃) Production Example 5-1 75:25 1,500 Production Example 5-2 75:25 1,550 Production Example 5-3 75:25 1,630 Production Example 5-4 75:25 1,650 Production Example 5-5 75:25 1,700

[0101]

Table 7

[0102]

[0103] *Units of Al2O3, AlN and AlON: weight %

[0104] Aluminum oxide reacts with aluminum nitride at a certain temperature to form an aluminum oxynitride phase. Although the aluminum oxynitride phase has high electrical insulation, it has low thermal conductivity, so the formation of the aluminum oxynitride phase has a great influence on the physical property values. Figure 1 is an XRD graph showing the physical property values ​​of the ceramic base that vary depending on the sintering temperature. Figure 2 is a graph showing the correlation between the content of aluminum oxide and the sintering temperature. Figure 1 , Figure 2 As shown in Table 1, the sintering temperature of 1,500°C was not sintered, the volume resistance could not be measured, and the measured thermal conductivity and density were very low. The analysis results of the XRD chart showed that the aluminum oxynitride phase was generated at a sintering temperature of 1,650°C or above. The larger the aluminum oxynitride content, the higher the volume resistance, but the thermal conductivity tended to decrease sharply. Therefore, it can be seen that the sintering in the present invention is preferably performed at a temperature lower than 1,650°C.

[0105] [Examples 9 to 20, Comparative Examples 9 to 20] Ceramic base manufacturing

[0106] According to the experimental results of the manufacturing example 5-3, the raw materials were mixed according to the composition of the following Table 8, and a small amount of ethanol and polyvinyl butyral (binder) were mixed and dried. Then, the dried mixture was stamped and processed to produce a preform, and then degreased at 500°C for 30 hours, and then the degreased preform was sintered and ground in a high-temperature pressure sintering furnace (pressure of 250 bar, temperature of 1,630°C) to produce a ceramic base.

[0107]

Table 8

[0108]

[0109]

[0110]

[0111] *Dopant unit: weight %

[0112] [Experimental Example 2] Evaluation of volume resistance and thermal conductivity of ceramic base (2)

[0113] After applying a voltage of 500 V / mm to each of the ceramic bases manufactured in Examples 9 to 20 and Comparative Examples 9 to 20, the current was measured (measured in a vacuum atmosphere and at room temperature) after one minute, and the volume resistivity was calculated. The results are shown in Table 9 below.

[0114] In addition, for each ceramic base manufactured in Examples 9 to 20 and Comparative Examples 9 to 20, samples were prepared using LFA 467 equipment from NETZSCH according to ASTM C0408-88R11, and then measured at room temperature to calculate the thermal conductivity. The results are also shown in Table 9 below.

[0115] In addition, the density value of each of the ceramic susceptors manufactured in Examples 9 to 20 and Comparative Examples 9 to 20 was calculated by the Archimedean method, and the results are also shown in Table 9 below.

[0116]

Table 9

[0117]

[0118]

[0119] The volume resistivity and thermal conductivity of each ceramic base manufactured in Examples 9 to 20 and Comparative Examples 9 to 20 were measured, and the results are shown in Table 9. The ceramic bases of Examples 9 to 20 all meet the volume resistivity (1.0E+10Ω·cm to 1.0E+13Ω·cm) at 500°C required by the new generation semiconductor manufacturing process.

[0120] Furthermore, with respect to thermal conductivity, from the comparison between Examples 9 to 11 and Comparative Examples 9 to 11, the comparison between Examples 12 to 14 and Comparative Examples 12 to 14, the comparison between Examples 15 to 17 and Comparative Examples 15 to 17, and the comparison between Examples 18 to 20 and Comparative Examples 18 to 20, it can be confirmed that Examples 9 to 20 using each dopant content of 0.05 to 0.5 weight % are superior to Comparative Examples 9 to 20 using any dopant content exceeding 0.05 to 0.5 weight %.

[0121] On the other hand, when GNP (graphene nanopowder) was added as a dopant in addition to MgO, when less than 0.05 wt% of GNP was used, the effect was minimal, and when 0.05-0.5 wt% was used, the thermal conductivity was improved. Moreover, when the content of GNP exceeded 0.5 wt%, the volume resistivity, density and hardness showed a sharp decline.

[0122] Furthermore, when nano-sized yttrium oxide (Y2O3) is added as a dopant in addition to MgO and GNP, when 0.05 to 0.5 wt% is used, the sinterability is improved and the volume resistance and thermal conductivity are increased. However, when yttrium oxide is used in an amount exceeding 0.5 wt%, a large amount of second phases such as YAP, YAM, and YAG are formed due to the reaction with alumina, and the thermal conductivity tends to decrease.

[0123] Furthermore, it can be confirmed that when rare earth composite oxides are added as dopants in addition to MgO, GNP and Nano Y2O3, if 0.05 to 0.5 wt% is used, the volume resistance and thermal conductivity tend to increase, and the density and hardness also increase. On the contrary, when the rare earth composite oxide content exceeds 0.5 wt%, the volume resistance and thermal conductivity tend to decrease sharply.

[0124] Furthermore, when comparing Example 11 and Comparative Example 10, Example 11 used 0.5 wt% MgO, while Comparative Example 10 used 1 wt% MgO. Although the difference in content was not significant, the thermal conductivity dropped sharply when the MgO content increased from 0.5 wt% to 1 wt%. This is because if the MgO content exceeded 0.5 wt%, an excessive amount (over 0.6 wt%) of MgAl2O4 phase or MgAlON phase was generated in the final product, resulting in an increase in the fraction. This result can be confirmed by the following Table 10.

[0125]

Table 10

[0126]

[0127] *Dopant unit: weight %.

Claims

1. A ceramic base, characterized in that: The ceramic base comprises aluminum oxide and aluminum nitride. The ceramic base does not contain a second phase including an aluminum oxynitride phase.

2. The ceramic base according to claim 1, characterized in that: The content of the aluminum oxide is more than 68 wt % and less than 99.8 wt %, and the content of the aluminum nitride is more than 0.2 wt % and less than 32 wt %.

3. The ceramic base according to claim 1, characterized in that: The ceramic base further includes any one or more dopants selected from magnesium oxide, yttrium oxide, graphene and rare earth composite oxides.

4. The ceramic base according to claim 3, characterized in that: The dopant is contained in an amount of 0.05 to 2 parts by weight relative to 100 parts by weight of the total weight of the aluminum oxide and the aluminum nitride.

5. The ceramic base according to claim 3, characterized in that: The dopant comprises magnesium oxide and graphene, With respect to 100 parts by weight of the total weight of the aluminum oxide and the aluminum nitride, 0.05 to 0.5 parts by weight of the magnesium oxide is included, and 0.05 to 0.5 parts by weight of the graphene is included.

6. The ceramic base according to claim 3, characterized in that: The dopant includes magnesium oxide, graphene and yttrium oxide, Relative to 100 parts by weight of the total weight of the aluminum oxide and the aluminum nitride, 0.05 to 0.5 parts by weight of the magnesium oxide, 0.05 to 0.5 parts by weight of the graphene, and 0.05 to 0.5 parts by weight of the yttrium oxide are included.

7. The ceramic base according to claim 3, characterized in that: The dopant includes magnesium oxide, graphene, yttrium oxide and rare earth composite oxides. Relative to 100 parts by weight of the total weight of the aluminum oxide and the aluminum nitride, 0.05 to 0.5 parts by weight of the magnesium oxide, 0.05 to 0.5 parts by weight of the graphene, 0.05 to 0.5 parts by weight of the yttrium oxide, and 0.05 to 0.5 parts by weight of the rare earth composite oxide are included.

8. The ceramic base according to claim 1, characterized in that: The volume resistivity of the ceramic base at 500° C. is 1.0E+10 to 1.0E+13Ω·cm, and the thermal conductivity at room temperature is above 30W / mk.

9. The ceramic base according to claim 3, characterized in that: The volume resistivity of the ceramic base at 500° C. is 1.0E+10 to 1.0E+13Ω·cm, and the thermal conductivity at room temperature is 40 to 60W / mk.

10. A ceramic base, characterized in that: The ceramic base comprises aluminum oxide and a dopant, The dopant includes any one or more of magnesium oxide, yttrium oxide, graphene and rare earth composite oxides.

11. The ceramic base according to claim 10, characterized in that: The content of the aluminum oxide is 98-99.95% by weight, and the content of the dopant is 0.05-2% by weight.

12. The ceramic base according to claim 10, characterized in that: The dopant includes magnesium oxide, yttrium oxide, graphene and rare earth composite oxides. The invention comprises 0.05 to 0.5 wt % of the magnesium oxide, 0.05 to 0.5 wt % of the yttrium oxide, 0.05 to 0.5 wt % of the graphene, and 0.05 to 0.5 wt % of the rare earth composite oxide.

13. A method for manufacturing a ceramic base, used for manufacturing the ceramic base according to claim 1, characterized in that: include: Step a), mixing aluminum oxide, aluminum nitride, an alcohol compound and a binder; Step b), drying the mixture to produce a powder after removing the alcohol compound component; Step c), compressing and molding the dried powder to produce a preformed body processed into a certain shape; Step d), degreasing the preform to remove the binder component; as well as Step e) sintering and grinding the degreased preform.

14. The method for manufacturing a ceramic base according to claim 13, characterized in that: The sintering in step e) is performed at a temperature less than 1,650°C.

15. The method for manufacturing a ceramic base according to claim 13, characterized in that: In the step a), any one or more dopants selected from magnesium oxide, yttrium oxide, graphene and rare earth composite oxides are added and mixed.

16. A method for manufacturing a ceramic susceptor, used for manufacturing the ceramic susceptor according to claim 10, characterized in that: include: Step a), mixing aluminum oxide, a dopant, an alcohol compound and a binder; Step b), drying the mixture to produce a powder after removing the alcohol compound component; Step c), compressing and molding the dried powder to produce a preformed body processed into a certain shape; Step d), degreasing the preform to remove the binder component; as well as Step e), sintering and grinding the degreased preform, The dopant includes any one or more of magnesium oxide, yttrium oxide, graphene and rare earth composite oxides.

Citation Information

Patent Citations

  • Preparation method of dense sintering type composite aluminum nitride ceramics

    CN109761616A

  • Substrate support structure and method of manufacturing the same

    CN115595562A

  • Aluminum nitride ceramic material as well as preparation method and application thereof

    CN116813352A

  • Production of aluminum nitride ceramic

    JP1996067565A

  • Sintered ceramics for electrostatic chuck and manufacturing method of the same

    KR1020170141340A